Photoelectron momentum distributions with twisted attosecond X waves carrying orbital angular momentum - Zhang, Xiaofan; Ma, Xiaomeng (Frontiers in Physics, 2023)
We theoretically investigate the photoelectron momentum distributions of 1s and 2p_x,y states of hydrogen by twisted attosecond X waves carrying orbital angular momentum based on first-order perturbation theory. The photoionization spectra as a function of photoelectron energy and emission angle are analyzed respectively. The results indicate that there are interference fringes in the energy spectra and more lobed structures in the angular distributions, which are attributed to the temporal-spatial structure of X waves. A concise formula is developed that can not only elucidate the physical mechanism of the interference fringes of energy spectra but also reproduce the numerical results. Moreover, we find that the angular distributions can reveal information that is hardly revealed in energy spectra, such as the structure of orbitals and X waves. Meanwhile, we also derive an equation that can quantitatively describe the respective effect of orbitals and X waves on photoelectron angular distributions. Our work provides an elaborate analysis on the photoelectron spectra in the twisted waves on the attosecond timescale.